(3GdMeGjI GdOSJhQjI ddMbhb hGdMQjGJ GdCSGSjI YHQ GdOYhi GdGMJjGWjI aj GdfXe GdOSJhQjI GdeYGUQI (B/s - (3MShfI, eMeO Ydjs ((3GdEScfOQjI, eUQ (B:s (3OGQ GdacQ GdLGeYj,s, 2018)
(3gOaJ GdOQGSI Edi GdJYQa Ydj GdMeGjI GdOSJhQjI ddMbhb hGdMQjGJ GdCSGSjI YHQ GdOYhj GdGMJjGWjI aj GdfXe GdOSJhQjI GdeYGUQI, GfJgLJ GdOQGSI GdefgL GdJMdjdj, hJchfJ gjcdjI GdOQGSI ef KdGK aUhd QFjSjI GdaUd GdChd (B: (3eGgjI GdOYhj GdOSJhQjI GdGMJjGWjI dMeGjI GdMbhb hGdMQjGJ GdCSGSjI, GdaUd GdKGfj (B: (3GdfXGe GdbGfhfj ddOYhj GdOSJhQjI GdGMJjGWjI dMeGjI GdMbhb hGdMQjGJ GdCSGSjI, GdaUd GdKGdK (B: (3GdJWHjbGJ GdMGdjI ddOYhj GdOSJhQjI GdGMJjGWjI heOj GdMGLI Edi GdYed HgG aj eUQ hGNJJeJ GdOQGSI HGSJYQGV GHQR GdfJGFL GdJj JhUdJ GdjgG hefgG, Cf GdQbGHI GdbVGFjI Yf WQjb GdOYhj GdGMJjGWjI GdeHGTQI hGdJj JYO CMOj JWHjbGJ GdOYhj GdOSJhQjI GdGUdjI gj OYhj bVGFjI efUhU YdjgG UQGMI aj GdOSGJjQ GdJj GbQJgG ef NdGd Jecjf CUMGH GdTCf ef egGLeI GdJTQjYGJ hGdGYeGd hGdJUQaGJ GdUGOQI ef GdSdWI GdYGeI, hGdJj JeKd GfJgGckG dMbhbge hMQjGJge GdCSGSjI(B.s
(3HHdjhLQGajI (B: (3UaMI (B179-185.s
Keywords: (3Mbhb GdEfSGfs -- (3bhGfjf hJTQjYGJs; (3GdMbhb GdeOfjIs -- (3bhGfjf hJTQjYGJs; (3GdMQjI GdSjGSjIs -- (3bhGfjf hJTQjYGJs